NARASI KEJIWAAN DALAM PUISI REFLECTION DAN ANXIENTY KARYA LANG LEAV (Psychological Narrative of Lang Leav’s Two Poems Reflection and Anxiety) - I Gusti Agung Sri Rwa Jayantini; Ni Komang Arie Suwastini; Ronald Umbas (SAWERIGADING, 2022)
Poetry as a literary work may carry various messages of humanity and mental conditions. This study compares two poems entitled Reflection and Anxiety, which are inspired by psychological aspects of human being. The poems were written by Lang Leav, a female writer who gained popularity as International Bestselling Author through her poetry and prose. By applying the descriptive method in literary research, the comparison of the two poems’ narratives resulted in two findings. First, the similarities of the poems can be identified from the psychological themes expressed by distinctive diction, namely suggestive words, the use of parallelism and repetition to strengthen the expression as well as antithesis to delineate the contradictory situation. Second, the difference was identified from the psychological theme showing the feeling established in the poem. The poem “Reflection” shows that when a person can feel calmness, he/she is able to advise himself/herself to face various life’s obstacles. On the other hand, the poem “Anxiety” describes the psychological disorder that often exists and must be faced by compromising the weaknesses and strengths of anxiety.